THE EFFECT OF JOB SATISFACTION, WORK ENVIRONMENT, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE PRODUCTION SECTION OF PT XYZ LAMPUNG - Hamildan, Zerylke Jovanian; Sayekti, Wuryaningsih Dwi; Ismono, Raden Hanung (Lampung University, 2025)
This study aims to analyze the level of job satisfaction, work motivation, employee performance, and the condition of work environment; the magnitude of the influence of job satisfaction and work environment on employee performance both direct and indirect ; and the magnitude of the influence of work motivation on employee performance. Data collection was carried out at PT XYZ Lampung from December 2022 to January 2023. This research was conducted using survey method involving 63 employees of production department. The data gathered from survey were analyzed using descriptive analysis and path analysis. The results show that production employees are satisfied with their jobs at PT XYZ. Meanwhile, work motivation, employee performance, and work environment are categorized as good. This study indicates that job satisfaction has a greater direct effect through work motivation on employee performance. In reverse, the work environment has a greater indirect effect on employee performance, both through work motivation and job satisfaction. Key words: employee performance, job satisfaction, path analysis, work environment, work motivation